Can After Sale Service Generate Brand Equity - Ahmad, S.; Butt, Mohsin (Emerald Group Publishing Limited, 2012)
Purpose – This research attempts to empirically expand the Aaker's consumer based brand equity model in hybrid business firms by incorporating after sales service as a new dimension. Exploring and understanding the drivers of consumer based brand equity in a hybrid business context will help in building industry specific competitive barriers and generating brand wealth. Design/methodology/approach – The data were collected from Pakistani adults using a structured questionnaire based on established scales. Convenience sampling was used to gather data from 205 respondents across the major cities of Pakistan. To test the proposed research model the data were analyzed using confirmatory factor analysis. Findings – The results support the proposed five‐factor model of consumer based brand equity for the automotive industry. The results support the notion that after sales service is related but is a separate dimension of consumer based brand equity in the automotive sector.Research limitations/implications – This proposed CBBE model was tested in the automotive sector of Pakistan. However, the automotive industry is special in the sense that it builds brands at dual level. This study only investigates consumer based brand equity at marque level. Future studies can expand on this work by investigating consumer based brand equity both at marque and model levels. Practical implications – The establishment of after sale services as a separate but independent dimension of consumer based brand equity for the hybrid business organizations provides a fresh reminder regarding the possibilities of new sources for building brand equity. Managers can focus on delivering excellent after sale services to build and enhance the equity of their brands in hybrid business organizations. Originality/value – This study expands Aaker's brand equity model by empirically establishing after sales service as a fifth dimension for the firms operating on hybrid business model.